2015
DOI: 10.1007/s10657-015-9483-2
|View full text |Cite
|
Sign up to set email alerts
|

Deterrence works for criminals

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Recent research on a criminal population, for example, has found that inmates respond similarly to risk and deterrence as student populations, although there is a higher percentage of inmates who tend to be risk seeking compared to students. (29) While the criminal population is likely to differ from terrorist populations, this result suggests that research in regards to risk and decision making may have applicability in other populations thought to differ greatly compared to our student population. Second, while individual data on terrorist decision making are scarce, evidence seems to suggest that planners of attacks take into account the expected costs and benefits in their decisions.…”
Section: Experimental Designmentioning
confidence: 89%
“…Recent research on a criminal population, for example, has found that inmates respond similarly to risk and deterrence as student populations, although there is a higher percentage of inmates who tend to be risk seeking compared to students. (29) While the criminal population is likely to differ from terrorist populations, this result suggests that research in regards to risk and decision making may have applicability in other populations thought to differ greatly compared to our student population. Second, while individual data on terrorist decision making are scarce, evidence seems to suggest that planners of attacks take into account the expected costs and benefits in their decisions.…”
Section: Experimental Designmentioning
confidence: 89%
“…The experimenter endows one participant with an electronic entitlement that is exchanged against real money at the end of the experiment (skirting the doctrinal question whether this constitutes theft or computer fraud). Another participant has the possibility to take some or all of this endowment (Falk and Fischbacher 2002, Gravert 2013, Harbaugh, Mocan et al 2013, Pecenka and Kundhlande 2013, Feess, Schramm et al 2014, Engel and Nagin 2015, Khadjavi 2015, Fleming, Parravano et al 2016. Participants even do so if stealing reduces expected profit (Schildberg-Hörisch and Strassmair 2012, Engel and Nagin 2015).…”
Section: Crime A) Theftmentioning
confidence: 99%
“…Time series analysis suggests that this increase in the severity of the sanction indeed led to the intended effect (Campbell andRoss 1968, Glass 1968). Khadjavi (2015) tests prison inmates on a game with the threat of sanctions, and finds that they react to the threat, but less so than students. Surprisingly, however, Schildberg-Hörisch and Strassmair (2012) find an increase in stealing if the expected value of the sanction increases, as long as the expected value of stealing remains positive.…”
Section: A) Deterrencementioning
confidence: 99%
“…The experimenter endows one participant with an electronic entitlement that is exchanged against real money at the end of the experiment (skirting the doctrinal question whether this constitutes theft or computer fraud). Another participant has the possibility to take some or all of this endowment (Falk and Fischbacher 2002, Gravert 2013, Harbaugh, Mocan et al 2013, Pecenka and Kundhlande 2013, Feess, Schramm et al 2014, Engel and Nagin 2015, Khadjavi 2015, Fleming, Parravano et al 2016. Participants even do so if stealing reduces expected profit (Schildberg-Hörisch andStrassmair 2012, Engel andNagin 2015).…”
Section: Crime A) Theftmentioning
confidence: 99%
“…Time series analysis suggests that this increase in the severity of the sanction indeed led to the intended effect (Campbell andRoss 1968, Glass 1968). Khadjavi (2015) tests prison inmates on a game with the threat of sanctions, and finds that they react to the threat, but less so than students. Surprisingly, however, Schildberg-Hörisch and Strassmair (2012) find an increase in stealing if the expected value of the sanction increases, as long as the expected value of stealing remains positive.…”
Section: A) Deterrencementioning
confidence: 99%